LEXICOGRAPHIC FOUNDATIONS OF CREATING AN UZBEK LANGUAGE ELECTRONIC THESAURUS - Xolyorova Gulruxsor G‘ayratovna (Western European Studies, 2025)
This article is dedicated to the lexicographic study of creating an Uzbek language electronic thesaurus, in which the importance of various fields of linguistics, including semantics, ontology, and terminology, is discussed. The article examines the analysis of linguistic thesauri's linguistic models using world experience, and provides a scientific approach to the issues of word classes, semantic classification, and structure. The effectiveness, functional possibilities, and theoretical conclusions of different types of thesauri are analyzed comparatively. Additionally, suggestions are developed for applying and utilizing ontological and terminological principles in creating the Uzbek language electronic thesaurus. The article discusses conceptual approaches aimed at forming a national linguistic model and methods based on international experience.
Keywords: electronic thesaurus; ideographic dictionary; linguistic ontology